The Influence of Natural Disasters, Road Infrastructure Quality, Social Assistance Expenditure, and the Human Development Index on Regional Economic Growth in Indonesia - Feny Fadiya; Armin Rahmansyah Nasution (Universitas Negeri Semarang, 2026)
This study examines how environmental vulnerability and development capacity shape regional economic growth across 34 Indonesian provinces during 2020–2024. Addressing a gap in endogenous growth and regional resilience literature, the study investigates whether natural disaster risk, road infrastructure quality, social assistance expenditure, and the Human Development Index (HDI) exert differential effects on provincial economic performance. Annual panel data were analyzed using a Fixed Effect Model, selected through model specification tests to control for unobserved provincial heterogeneity. The findings indicate that natural disaster risk significantly suppresses economic growth by disrupting productive assets and economic activities, whereas HDI positively promotes growth through improvements in human capital quality. In contrast, road infrastructure quality and social assistance expenditure do not exhibit significant effects, suggesting that their growth impacts may depend on implementation efficiency, institutional capacity, and longer-term transmission mechanisms. These results highlight the predominance of human capital and disaster resilience over short-term fiscal interventions in shaping regional development outcomes. The study extends endogenous growth theory by integrating environmental risk and regional resilience perspectives within a subnational development context in a disaster-prone developing economy.